2006
DOI: 10.1128/aem.72.3.1980-1987.2006
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative PCR Confirms Purity of Strain GT, a Novel Trichloroethene-to-Ethene-Respiring Dehalococcoides Isolate

Abstract: A novel Dehalococcoides isolate capable of metabolic trichloroethene (TCE)-to-ethene reductive dechlorination was obtained from contaminated aquifer material. Growth studies and 16S rRNA gene-targeted analyses suggested culture purity; however, the careful quantitative analysis of Dehalococcoides 16S rRNA gene and chloroethene reductive dehalogenase gene (i.e., vcrA, tceA, and bvcA) copy numbers revealed that the culture consisted of multiple, distinct Dehalococcoides organisms. Subsequent transfers, along wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
225
0
4

Year Published

2009
2009
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(240 citation statements)
references
References 28 publications
11
225
0
4
Order By: Relevance
“…CN-Cbl was depleted at higher rates in the 25 mg l 21 CN-Cbl-amended Dehalococcoides cultures. At day 17, when BAV1 cultures had completely dechlorinated cis-DCE to ethene, CN-Cbl concentrations dropped to 0.7 + 0.1 mg l 21 , averaging an uptake rate of 1500 ng l 21 qPCR analysis demonstrated that limiting amounts of 1 mg l 21 CN-Cbl affected Dehalococcoides growth yields, which were calculated as described [22]. For example, 1.4 + 0.8 Â 10 7 BAV1 cells per mmole of Cl 2 released were obtained in cultures amended with 1 mg l 21 CN-Cbl, whereas 1.3 + 0.1 Â 10 8 BAV1 cells per mmole of Cl 2 released (a 9.1-fold increase) were measured in cultures amended with 25 mg l 21 CN-Cbl (table 1).…”
Section: (E) Other Analytical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CN-Cbl was depleted at higher rates in the 25 mg l 21 CN-Cbl-amended Dehalococcoides cultures. At day 17, when BAV1 cultures had completely dechlorinated cis-DCE to ethene, CN-Cbl concentrations dropped to 0.7 + 0.1 mg l 21 , averaging an uptake rate of 1500 ng l 21 qPCR analysis demonstrated that limiting amounts of 1 mg l 21 CN-Cbl affected Dehalococcoides growth yields, which were calculated as described [22]. For example, 1.4 + 0.8 Â 10 7 BAV1 cells per mmole of Cl 2 released were obtained in cultures amended with 1 mg l 21 CN-Cbl, whereas 1.3 + 0.1 Â 10 8 BAV1 cells per mmole of Cl 2 released (a 9.1-fold increase) were measured in cultures amended with 25 mg l 21 CN-Cbl (table 1).…”
Section: (E) Other Analytical Methodsmentioning
confidence: 99%
“…Methane, ethene and chlorinated ethenes were quantified using an Agilent 7890 gas chromatograph equipped with a flame ionization detector and a DB-624 capillary column (60 m  0.32 mm  1.8 mm) as described [22]. Acetate was analysed using an Agilent 1200 series HPLC system equipped with an Aminex HPX-87H column (Bio-Rad, Hercules, CA, USA).…”
Section: (E) Other Analytical Methodsmentioning
confidence: 99%
“…(Dhc) (MaymoGatell et al, 1997). Dhc containing the gene tceA have been found to respire TCE and cis-DCE (Seshadri et al, 2005) whereas Dhc with the genes vcrA or bvcA respire cis-DCE and vinyl chloride (VC) (Muller et al, 2004;Sung et al, 2006). Several recent laboratory studies have also suggested that abiotic degradation pathways for chlorinated ethenes are of importance in the presence of iron minerals (Darlington et al, 2008;Ferrey et al, 2004;He et al, 2008He et al, , 2010Jeong et al, 2011;Lollar et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Genome sequences exist for several OHRB, including five Dehalococcoides mccartyi strains [13][14][15][16] and Dehalogenimonas lykanthroporepellens strain BL-DC-9 [17] within the Chloroflexi; Geobacter lovleyi strain SZ [18] and Anaeromyxobacter dehalogenans strains 2CP-C and 2CP-1 [19] from the Proteobacteria; and Desulfitobacterium hafniense strains Y51 and DCB-2 [6,20], Desulfitobacterium dehalogenans (NC_018017), Desulfitobacterium dichloroeliminans (NZ_AGJE00000000) and most recently two Dehalobacter strains [21] from the Firmicutes. Given the low cost and broad availability of sequencing from pure or mixed cultures, the number of OHRB genomes will increase rapidly.…”
Section: Organohalide Respirationmentioning
confidence: 99%